El material didáctico específico para el desarrollo del pensamiento lógico-matemático en las niñas y niños de 4 a 5 años de la unidad educativa “Emiliano Ortega Espinoza” del cantón Catamayo, provincia de Loja, Periodo 2014- 2015 - Peña Pinto, Glenda Elizabeth (2016)
This research includes a study. The specific teaching materials for the development of mathematical logical thinking in children from 4 to 5 years Education Unit Emiliano Ortega Espinoza Canton Catamayo Loja Province. Period 2014 - 2015. The overall objective raised is to contribute to the development of mathematical logical thinking through the specific teaching materials on child and children 4 to 5 years of the educational unit Emiliano Ortega Espinoza Canton Catamayo, Loja Province, Period 2014 - 2015.Para the development of this research we used methods, techniques and tools in the research process methods used are: scientific, analytical and synthetic, hermeneutical, statistical method. The technique used was direct observation and the instrument to collect field data was Skills Table CHRISTINE MILER, which will serve to verify the degree of development with regard to the logical-mathematical thinking. For the development of this research a population of 22 children were counted. With the results obtained it can verify that 65% of children do not have sufficiently developed their logical-mathematical thinking for his age and the teacher does not use specific materials for teaching and learning and that 35% if you have it on acceptable terms. So we conclude that the teacher should use methodological strategies to develop logical- mathematical thinking in children of the school